Eamcet - Maths - Hyperbolic Functions

(cosh x/1- tanh x)+(sinh x/ 1- coth x)=

A.  2 cosec hx

B.  sinh x+ cosh x

C.  sech x

D.  tanh x

View Answer  

Correct Answer :

sinh x+ cosh x



Explanation :
No Explanation available for this question

(cosh x+ sinh x)n=

A.  cosh nx+ sinh nx

B.  tanh nx6coth nx

C.  coth nx+sech nx

D.  sinh nx+cosech nx

View Answer  

Correct Answer :

cosh nx+ sinh nx



Explanation :
No Explanation available for this question

If tan A= tan α tan β= cot α tanh β, then tan(A+B)=

A.  sinh 2βcos 2α

B.  sinh 2β cosec 2α

C.  cosh 2βsec 2α

D.  cosh 2β tan 2α

View Answer  

Correct Answer :

sinh 2β cosec 2α



Explanation :
No Explanation available for this question

If 2 Sinh-1 (a/√(1-a2))= log(1+x/1-x), then x=

A.  2a

B.  3a

C.  4a

D.  a

View Answer  

Correct Answer :

a



Explanation :
No Explanation available for this question

If sinh 9- k sinh k=(k+1)sinh3 k,then k=

A.  3

B.  4

C.  9

D.  noneof these

View Answer  

Correct Answer :

3



Explanation :
No Explanation available for this question

If Sinh-1 √3= log(sec θ+tan θ), then θ=

A.  π/6

B.  π/4

C.  π/3

D.  2 π/3

View Answer  

Correct Answer :

π/3



Explanation :
No Explanation available for this question

If z= x+iy such that cos z= 2, then z=

A.  log(2+√3)

B.  log(2+√3)

C.  log(2+√5)

D.  log(2-√3)

View Answer  

Correct Answer :

log(2-√3)



Explanation :
No Explanation available for this question

(tan hx/ Sechx-1)+ (sinh x/ sech x+1)

A.  -2 cosech x

B.  sin hx+ cos hx

C.  sech x

D.  tanh x

View Answer  

Correct Answer :

-2 cosech x



Explanation :
No Explanation available for this question

If A= Tanh-1 (1/2)+ Coth-1(2), B= sinh(Cosh-1 9), C= sech2(Tanh-1 1/2)+cosech2(Coth-1 3) then

A.  A

B.  A

C.  B

D.  B

View Answer  

Correct Answer :

A<B<C



Explanation :
No Explanation available for this question

If cosh x= sec θ, then tanh2 x/2=

A.  sin2 θ/2

B.  cos2 θ/2

C.  tan2 θ/2

D.  cot2 θ/2

View Answer  

Correct Answer :

tan2 θ/2



Explanation :
No Explanation available for this question

log(x-1+√(x2-2x)(x≥2) is equal to

A.  Sinh-1 (x-1)

B.  Sinh-1 (x+1)

C.  Cosh-1 (x-1)

D.  Cosh-1 (x+1)

View Answer  

Correct Answer :

Cosh-1 (x-1)



Explanation :
No Explanation available for this question

2 cosh 3 cosh 5=

A.  cosh 2

B.  cosh 8- cosh 2

C.  cosh 15

D.  cosh 8+ cosh 2

View Answer  

Correct Answer :

cosh 8+ cosh 2



Explanation :
No Explanation available for this question

If coth x= sec θ, then cosech x=

A.  cosec θ

B.  sec θ

C.  tan θ

D.  cot θ

View Answer  

Correct Answer :

tan θ



Explanation :
No Explanation available for this question

If y= 1/2 Cosech-1 (1/2x√(1+x2)), then x=

A.   cosh y

B.  sinh y

C.  tanh y

D.  coth y

View Answer  

Correct Answer :

sinh y



Explanation :
No Explanation available for this question

If sinh x= cos θ and sin θ=2/3 then cosh x=

A.  5/3

B.  √13/3

C.  √14/3

D.  none

View Answer  

Correct Answer :

√14/3



Explanation :
No Explanation available for this question